Pengaruh Tegakan Sengon (Paraserianthes falcataria L.) terhadap Kandungan C, N Tanah dan Produktivitas Buah Perkebunan Salak - Diah Ayuretnani Handayani; I Gusti Putu Suryadarma (Jurnal Ilmu Kehutanan, 2022)
The difference between agroforestry and monoculture planting system is the presence of organic materials input from the canopy tree or the roots. The study aimed to determine factors affecting micro-climate conditions, soil nutrients of C, N and to identify the influence of sengon plantation on snake fruits productivity. This research used the observation method and was conducted in Gadung village, Bangunkerto, Turi. The treatments were the location used pattern monoculture system (control), agroforestry with trees along borders (AFS), and full trees (AFT). The soil was sampled compositely one diagonal. Analyses descriptive and regressions were used to analyze data of the soil nutrient with the treatment and fruit productivity. The results showed that the presence of Sengon on salak plantation influenced micro-climates conditions due to canopy cover by sengon. A location AFT showed the highest value of C-org (1.7%), and N (0.1%) in all plots. Meanwhile, the productivity of fruits on the monoculture system showed the highest fruit production that was 1150 kg/ha. However, the results were not significantly different from AFS and AFT. The snake fruit productions of AFT and AFS were 1035 and 1085 kg/ha, respectively. The results suggested that sengon plantations increased soil fertility, i.e., C and N...